Postmodern study: analysis of themes and techniques in the crying of Lot 49, slaughterhouse-five and disgrace - Islam, Shawlion (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2016.